Inheritance of Historical Values in the Community Through Puppet Art Media in Tegal Regency - Wulandari, Ratna Sri; Purnomo, Arif; Romadi, Romadi (Universitas Negeri Semarang, 2021)
The purpose of this study: (1) To know the historical themes unearthed by Dalang in Tegal regency. (2) To know how Dalang bequeaths historical values through puppets. (3) To know the obstacles and supports experienced by Dalang in passing on the historical value by a puppet in the Tegal regency. This study used the descriptive qualitative method, collecting data using observation, interview, and documentation. The analytical technique uses an interactive model of analysis. The result of this study shows that (1) The historical themes unheartened by dalang tell about local stories such as the origin of Slawi and out of the ethos of Mahabharata. (2) The messages that want to be delivered by aesthetic elements, and (3) the obstacles faced by puppet shows are the cost to carry on the puppet show, not all people can pay for it, and the support of people who are contentment to historical value and the pleasure about historical values and when dalang are getting older they also get many experiences and knowledge.